Claudin-1, -2 and -3 Are Selectively Expressed in the Epithelia of the Choroid Plexus of the Mouse from Early Development and into Adulthood While Claudin-5 is Restricted to Endothelial Cells - Steinemann, Alexandra; Galm, Isabel; Chip, Sophorn; Nitsch, Cordula; Maly, Ireneusz Piotr (Frontiers in Neuroanatomy, 2016)
A primary function of epithelial and endothelial monolayers is the formation of barriers that separate tissues into functional compartments. Tight junctions (TJs) seal the intercellular space between the single cells of a monolayer. TJs thus contribute importantly to the homeostasis of the cerebrospinal fluid as they help in maintaining the blood-brain-barrier (BBB) and the blood-cerebrospinal fluid barrier. The composition of TJs differs by its localization as well as the stage of development according to its respective function. Claudin-3 is typically present in the epithelia and has been claimed to be a constituent of the BBB. It is, however, notoriously difficult to demonstrate its expression in endothelial cells of the brain vasculature at the morphological level by means of immunohistochemical techniques. Using an improved fixation strategy (4 % paraformaldehyde at pH 11, in the presence of EDTA) and the sensitive alkaline phosphatase as a detection system, we show that claudin-3 is present in mouse epithelia from embryonic day 14 onwards. In brain, it is restricted to the anlage of choroid plexus in the ventricles, together with claudin-1 and -2. In adult mice, it is clearly delineating the epithelium of the choroid plexus in the lateral and fourth ventricles. In contrast, in cerebral blood vessels claudin-3 as well as claudin-1 and -2 are absent in cerebral blood vessels during all developmental stages up to adulthood. Rather, the BBB is characterized by the presence of claudin-5, ZO-1 and occludin. Thus, in mice claudin-3 is an important constituent of TJ in the embryonic and in the adult choroid plexus.